The impact of ESG performance on greenhouse gas emission performance in Latin America - Firmino, Anderson Luís (2025)
This study sought to examine the relationship between Environmental, Social, and Corporate Governance (ESG) performance and greenhouse gas (GHG) emission performance. Using a sample of Latin American companies, we analyzed the influence of ESG performance on GHG emission performance through both the overall ESG score and the individual scores attributed to the three ESG dimensions. ESG practices are complex, involving a broad group of stakeholders, each with different interpretations of their impact on organizations and society. Consequently, ESG reports include a variety of indicators and themes. Despite the growing recognition of ESG practices as key indicators of sustainable performance, a gap remains in Latin American studies regarding a more specific examination of the relationship between these criteria and corporate GHG emissions. These findings are relevant not only to the academic community but also to policymakers, regulators and business leaders seeking to address urgent climate challenges and promote sustainable practices. Research on this issue can help these agents better understand and assess future opportunities and risks related to ESG practices, evaluate efforts and results in GHG mitigation, allocate capital resources strategically, enhance legitimacy, and gain stakeholder support. Companies adopting sustainable practices have the potential to create positive impacts on employment and on local communities, generating significant social and economic benefits for their regions. In addition, firms in areas with higher ESG scores and better GHG mitigation performance may gain a competitive advantage, attracting environmentally conscious investors and consumers. The robust findings of this research are attributed to the efficacy of the hierarchical econometric model, which captures variations across multiple levels. These findings confirm the positive relationship between higher ESG scores and improved GHG emission performance. They also demonstrate a predominance of corporate-related characteristics in sustainability performance and emissions control, with national and temporal variations playing smaller roles. These results contribute to academic knowledge and suggest practical implications for addressing challenges associated with climate change, providing insights that can guide public policies and corporate strategies.